Phylogeography and genetic effects of habitat fragmentation on endemic Urophysa (Ranunculaceae) in Yungui Plateau and adjacent regions - Xie, Deng-Feng (PLoS One, 2017)
Urophysa is a Chinese endemic genus with only two species (U. rockii and U. henryi) distributed in Yungui Plateau (Guizhou Province) and adjacent regions (i.e., Provinces of Hunan, Hubei, Chongqing and Sichuan). The aim of this study was to determine the genetic diversity and population differentiation within Urophysa and investigate the effect of the Yungui Plateau uplift and climate oscillations on evolution of Urophysa. In this study, micro-morphological characteristics, nine microsatellite loci (SSR), two nuclear loci (ITS and ETS) and two chloroplast fragments (psbA-trnH and trnL-trnF) were used to analyze the phylogenetic relationships and assess genetic and phylogeographical structure of Urophysa. Isolation by distance (IBD) was performed to research the effects of geographical isolation. We detected high genetic diversity at the species level but low genetic diversity within populations. Striking genetic differentiation (AMOVA) among populations and a significant phylogeographical structure (N(ST) > G(ST), p < 0.01) were detected among U. henryi populations, along with significant effects of isolation by distance (IBD). Molecular clock estimation using calibration strategy and cpDNA substitution rate indicated that the divergence of U. henryi occurred during late Miocene to early Quaternary, when the orogeny of Yungui Plateau was violent. U. rockii originated at the early Quaternary and further differentiated at early Pleistocene. Our results suggested that habitat fragmentation played an important role in the genetic diversity and population differentiation of U. rockii and U. henryi. Heterogenous geomorphological configuration and complicated environment resulted from rapid uplift of the Yungui Plateau were inferred as important incentives for the modern phylogeograhpical pattern and species divergence of Urophysa. The geographical isolation, limited gene flow, specialized morphologies and the Pleistocene climatic oscillation greatly contributed to the allopatric divergence of U. rockii. Significant genetic drift and inbreeding were detected in these two species, in situ measures should be implemented to protect them.